A biomechanical comparison of unilateral and bilateral String-of-Pearls™ locking plates in a canine distal humeral metaphyseal gap model - Hurt, R. J.; Syrcle, J. A.; Elder, S.; McLaughlin, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
Objective: To compare the in vitro biomechanical performance of two String-of-Pearls (SOP) plate constructs in a canine distal humeral metaphyseal gap model.Methods: Seven pairs of canine cadaveric humeri, including the elbow joints, were prepared. One group consisted of a unilateral medially placed SOP plate with bicortical screws (UNI). The second group consisted of bilateral caudo-medial and caudo-lateral SOP plates applied with monocortical screws (BI). A 2 cm ostectomy was performed immediately proximal to the supratrochlear foramen. Constructs were tested in torsion and axial compression.Results: The UNI constructs had significantly lower stiffness in torsion and axial compression than the BI group. However, UNI constructs had a significantly higher ultimate strength than BI constructs. All UNI constructs failed by bending of the transcondylar screw and SOP plate. All BI constructs failed by axial pullout of the distal most screws.Clinical significance: In stabilizing canine supracondylar humeral fractures as modeled here, both the UNI model and the BI model demonstrated biomechanical advantages. The incorporation of a transcondylar screw through the medial plate appears to be beneficial to construct strength.
Keywords: Supracondylar humeral fracture; mechanical testing; humerus; SOP; String-of-Pearls plate